Gasa Gasa Girl Goes to Camp : A Nisei Youth Behind A World War II Fence - Havey, Lily Yuriko Nakai, 1932- (Book collections on Project MUSE., 2014)
"What should by now be a familiar, if always disturbing event in American history--the internment of Japanese American citizens and aliens during World War II--is given an original treatment in this creative memoir. Lily Havey was ten years old when her family of four was uprooted and sent first to Santa Anita Assembly Center in southern California and subsequently for the duration of the war to the Amache (or Granada) internment camp in southeastern Colorado. She experienced removal and confinement as a pubescent young woman and with a distinctly individual perspective. She was an independent and, in her own and apparently her parents' view, difficult child. Her mother called her a gasa gasa girl, meaning wiggly, restless, unable to sit still. The interment put additional stress on the dysfunctional marriage of her parents and especially on her father, who had a particularly hard time coping. Lily Havey's recounting of that time is in turn wrenching, funny, touching, and biting but consistently informative and engrossing, especially with regard to the daily challenges of life and the internees' adaptations"--